Recent progress in bio-mediated synthesis and applications of engineered nanomaterials for sustainable agriculture - Bora, Kainat Amin; Hashmi, Saud; Zulfiqar, Faisal; Abideen, Zainul; Ali, Haibat; Siddiqui, Zamin Shaheed; Siddique, Kadambot H. M. (Frontiers in Plant Science, 2022)
The ever-increasing demand for agricultural products in food, medicine, and other commercial sectors requires new technologies such as using advanced materials in agricultural practices and promoting smart utilization of natural resources. The application of engineered nanomaterials (ENMs) enhances the production and yield of various agricultural species while resisting harmful environmental stresses. Bio-mediated synthesis of ENMs is a time-efficient, low-cost, environmentally friendly, green technology. The precedence of using a bio-mediated route over conventional precursors for ENM synthesis is non-toxic, readily available, and possess many active agents that can facilitate the reduction and stabilization process during nanoparticle formation. They also provide an intra- or extra-cellular active site for nanoparticle growth with excellent stability. This review presents recent developments in bio-mediated ENMs and green synthesis techniques using plants, algae, fungi, and bacteria, including signiﬁcant contributions to identifying major ENM applications in agriculture with potential impacts on sustainability, such as the role of different ENMs in agriculture and their impact on different plant species. The review also covers the advantages and disadvantages of different ENMs and potential future research in this field.